أحاديث غير الكتب الستة في كتاب "التذكرة" للإمام القرطبي دراسة تخريجية نقدية للخمسين حديثا الأولى من المائة الخامسة - Mohd Amir (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
This research aims at a critique and extractive study of the first fifty hadith out of five hundred, as explored by Imam Qurtubi about the state of the dead and circumstances of the hereafter. The researcher felt the necessity of extracting the hadiths due to the great interest on the book Al-Tadhkirah which discusses about the hereafter to some people, the book Al-Tadhkirah contains many weaknesses and fabricated hadith therefore it doesn't deserve the right to be believed. The researcher has adopted this the inductive methodology by looking at the elevated hadiths described in the Al-Tadhkirah and their tafsir. The seminal work on the hadith by Imam Qurtubi relating to life after death is extremely crucial for a greater understanding on the hereafter. It is all the more relevant today given the rising scepticism among Muslims regarding the great chaos on the day of Resurrection.